A Novel Protein Elicitor (PELL1) Extracted from Lecanicillium lecanii Induced Resistance against Bemisia tabaci (Hemiptera: Aleyrodidae) in Gossypium hirsutum L. (23rd August 2022) - Basit, Abdul; Yaseen, Muhammad; Babar, Maham; Wang, Yong; Abdulle, Yusuf Ali; Qiu, Dewen; Li, Yunzhu; Bashir, Muhammad Amjad; Shahzad, Muhammad Sarmad; Farooq, Hasnain; Alajmi, Reem A.; Mangi, David N.; et al.
Abstract : Protein elicitors play a key role in signaling or displaying plant defense mechanism and emerging as vital tools for biocontrol of insects. This study was aimed at the characterization of the novel protein elicitor isolated from entomopathogenic fungi Lecanicillium lecanii (V3) strain and its activity against whitefly, Bemisia tabaci, in cotton ( Gossypium hirsutum L.). The sequence of purified elicitor protein showed 100% similarity with hypothetical protein LEL_00878 (Cordyceps confragosa RCEF 1005) (GenBank accession no. OAA81333.1). This novel protein elicitor has 253 amino acid residues and 762 bp with a molecular mass of 29 kDa. Their combatant protein was expressed in Escherichia coli using pET-28a (+) plasmid. Bioassay was revealed to quantify the impact of numerous concentrations of protein (i.e., 58.32, 41.22, and 35.41  μ g/ml) on the fecundity rate of B tabaci on cotton plants. Bioassay results exhibited a significant effect (P ≤ 0.001 ) of all the concentrations of protein on the fecundity rate of B. tabaci . In addition, the gene expression analysis found a significant upregulation of the major genes associated with salicylic acid (SA) and jasmonic acid (JA) defense pathways in elicitor protein-treated plants. Our results showed that the potential application of novel protein elicitor derived from Lecanicillium lecanii will be used as future biointensive controlling approaches against whitefly, Bemisia tabaci.